Compost Extracts of Vegetable Wastes as Biopesticide to Control Cucumber Mosaic Virus - WIWIEK SRI WAHYUNI; ARIE MUDJIHARJATI; NIKEN SULISTYANINGSIH (Bogor Agricultural University, Indonesia, 2010)
In semiaerobic conditions, different composting processes of vegetable wastes have different characteristics. When compost extracts amended with the effective microorganism-4 (EM4, +E) and Pseudomonas aeruginosa Ch1 (+B) stored for 40 days, the bacteria population and P-content increased. Tobacco plants treated with compost extracts amended with +E+B and [+E+B] directly to organic materials and inoculated with Cucumber mosaic virus (CMV) both sprayed or watered applications reduced the disease severity. This is due to the higher bacteria population in the root and rhizosphere, particularly the activities of P. aeruginosa Ch1 as plant growth promoting rhizobacteria (PGPR) rather than the activities of bacteria from EM4. The role of P. aeruginosa Ch1 to induce resistance of the plants to CMV was suggested by producing siderophores under the limited Fe conditions,17-20 ppm.